Liquid-Liquid Equilibria of Gluconic Acid between Water and Tri-n-Octylamine in various Diluent - Inci, Ismail (Asian Journal of Chemistry, 2010)
Gluconic acid, C6H12O7, is used for a large number of different industrial applications due to some exceptionally useful properties. However, data about gluconic acid and tri-n-octylamine/diluent system are not available in literature. The aim of this study is to investigate the extraction of gluconic acid from. aqueous solutions by tri-n-octylamine dissolved in a variety of diluents a in wide range of amine concentrations (0.23–1.72 mol/L). Extractin .equilibria of gluconic acid in the system solution of tri-n-octylamine in mixtures with 5 various solvents at temperature 298.15 K have been measured. Diluting solvents used in this study are hexane, cyclohexane, toluene, methyl isobutyl ketone (MIBK) and propanol. Using Bizek approach three acid : amine complexes, (Acid)·(Amine); (Acid)·(Amine)2 and (Acid)2 (Amine)3 have been assumed to exist in org ganic phase. As a result of batch extraction experiments distribution coefficients, loading factors and overall extraction constants were calculated.